Atomic scale analysis of grain boundary deuteride growth front in Zircaloy-4. (November 2018) - Breen, A.J.; Mouton, I.; Lu, W.; Wang, S.; Szczepaniak, A.; Kontis, P.; Stephenson, L.T.; Chang, Y.; da Silva, A.K.; Liebscher, C.H.; Raabe, D.; Britton, T.B.; et al.
Abstract: Zircaloy-4 (Zr-1.5%Sn-0.2%Fe-0.1%Cr wt%) was electrochemically charged with deuterium to create deuterides and subsequently analysed with atom probe tomography and scanning transmission electron microscopy to understand zirconium hydride formation and embrittlement. At the interface between the hexagonal close packed (HCP) α-Zr matrix and a face centred cubic (FCC) δ deuteride (ZrD1.5–1.65 ), a HCP ζ phase deuteride (ZrD0.25–0.5 ) has been observed. Furthermore, Sn is rejected from the deuterides and segregates to the deuteride/α-Zr reaction front. Graphical abstract: Unlabelled Image